From crisis to excellence : change management at Fre`re Hospital in the Eastern Cape (Case A) - Arnold, Bashierah (SAGE Knowledge. Cases., 2018)
Fre`re Hospital case A presents students with a decision dilemma within a highly challenging and dynamic South African context. The challenges faced by the protagonist, Dr Wagner, provide students with the opportunity to examine possible reactions and change management strategies when placed in a crisis management situation. There are multiple themes presented in the case that contribute to the dilemma facing Dr Wagner. Students must identify the key issues that caused the situation of crisis at the hospital, familiarise themselves with the key problems experienced by the hospital's management, staff and patients, and discuss what management approaches would be appropriate to address these problems. The case questions ask students to place themselves in Dr Wagner's shoes and decide whether or not each would choose to embrace the challenge of continuing as the hospital's CEO.